Matches Between Human Resources and Strategy Among Ncaa Basketball Teams - Wright, Patrick M.; Smart, Dennis L.; McMahan, Gary C. (Academy of Management Journal, 1995)
This study examined the relationships among strategy, human resources, and performance among National Collegiate Athletic Association (NCAA) basketball teams. Results based on survey data and a widely used performance rating indicated that coaches' preferred strategies influence the characteristics that they look for in recruits. Also, teams implementing a strategy different from a coach's preferred strategy performed less well than those implementing the preferred strategy. Finally, human resource capacities interacted with strategy in determining team performance for two different measures of performance.